REGULATION OF PARAMETERS OF NATURAL OSCILLATIONS OF THE SPATIAL FRAME OF THE BUILDING - E. K. Agachanov; G. M. Kravchenko; E. V. Trufanova (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
Aim. In article the problem of influence of geometrical characteristics of elements of a steel concrete frame of the building on parameters of forms of natural oscillations of system is considered.Methods. The finite and element model of an object in a program complex of ING + according to the spatial slabby and rod diagram is developed by the finite-element method. A slabby grillage, plates of overlapping and a covering, a wall and a diaphragm of rigidness were modelled by triangular cover elements with 18 levels of freedom and quadrangular cover elements with the 24th freedom levels. Columns were modelled by spatial rods with 12 levels of freedom. Spatial rigidness of a frame is provided with collaboration of columns, diaphragms of rigidness and plates of overlappings. The estimated diagram is developed taking into account rigid seal of columns, diaphragms of rigidness and walls in a monolithic slabby grillage.Results. Seven versions of different project solutions of a frame of the multi-storey building are probed. In project decisions parameters of a transverse section of walls of the elevator shaft, diaphragms of cruelty and plates of overlappings varied. As a result of dynamic calculation in a program complex of ING + MKE are received the maximum relocation of the upper point of a plate of overlapping, frequency and the periods of natural oscillations.Conclusion. The analysis of results of researches on regulation of forms and frequencies of natural oscillations of a frame of the building taking into account change of rigidities of elements of a frame is made. Results of dynamic calculation are reduced in plate, graphic and illustrative forms. Recommendations about a choice of version of project solutions of a frame of the building with optimum parameters of natural oscillations are made.